(untitled) (Global Journal of Medical Research, 2020)
Analysis of the leaf and stem essential oils from three Brazilian Lauraceae species showed that the major constituent of O. odorifera was safrole (57.1 and 88.5% for leaves and stems, respectively) while for O. indecora leaves the major ones were the α-pinene (12.8%) and β-pinene (12.4%) and β-bisabolol (12.2%) in the stems. For the third species, Persea venosa, the main components of leaf and stem oils were spathulenol (27.8 and 14.7%, respectively) and humulene epoxide II (11.3 and 5.1%, respectively). The bioactivity results indicated that the leaf essential oil from O. indecora was the most active for both radical scavenging activity (IC50=0.142 mg/mL) and cytotoxicity against human tumor cells, with growth inhibitions for the colon tumoral line HCT-116 (100%) and breast cancer cell line MCF-7 (99.2%), at 5 μg/mL concentration. This activity might be related to the presence of α-pinene and β-pinene in the leaf essential oil of O. indecora. However, further studies with the isolated compounds are necessary to fully understand these bioactivites.